2016
DOI: 10.1016/j.bbamcr.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Privileged crosstalk between TRPV1 channels and mitochondrial calcium shuttling machinery controls nociception

Abstract: The nociceptive noxious heat-activated receptor - TRPV1, conducts calcium and sodium, thus producing a depolarizing receptor potential, leading to activation of nociceptive neurons. TRPV1-mediated calcium and sodium influx is negatively modulated by calcium, via calcium-dependent desensitization of TRPV1 channels. A mitochondrial Ca uniporter - MCU, controls mitochondrial Ca entry while a sodium/calcium transporter - NCLX shapes calcium and sodium transients by mediating sodium entry into and removing calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 54 publications
2
33
0
Order By: Relevance
“…To mimic the capsaicin-induced current, we first introduced an inward current with the activation and inactivation kinetics resembling TRPV1-induced inward current evoked by short (5s) puff application of capsaicin (1 μM) into our single-compartment model (see Methods). The stimulation of the soma with a modeled 5 s application of capsaicin (capsaicin-like stimulation) resulted in an inward current and action potential firing, which resembled the experimental data (Figures 3C,D, compare to Supplementary Figure 2A,B respectively, see also Nita et al, 2016). …”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…To mimic the capsaicin-induced current, we first introduced an inward current with the activation and inactivation kinetics resembling TRPV1-induced inward current evoked by short (5s) puff application of capsaicin (1 μM) into our single-compartment model (see Methods). The stimulation of the soma with a modeled 5 s application of capsaicin (capsaicin-like stimulation) resulted in an inward current and action potential firing, which resembled the experimental data (Figures 3C,D, compare to Supplementary Figure 2A,B respectively, see also Nita et al, 2016). …”
Section: Resultssupporting
confidence: 79%
“…To that end, we simulated a current induced by application of capsaicin, an activator of the noxious heat-sensitive TRPV1 channel, expressed by nociceptive neurons. We and others have previously demonstrated that application of capsaicin produces depolarization of nociceptive neurons, followed by a stereotypic pattern of action potential firing (Nita et al, 2016; Blair and Bean, 2003; see also Supplementary Figure 2, here). To mimic the capsaicin-induced current, we first introduced an inward current with the activation and inactivation kinetics resembling TRPV1-induced inward current evoked by short (5s) puff application of capsaicin (1 μM) into our single-compartment model (see Methods).…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations